SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING BERBASIS WEB - Wahyu Pamungkas; Firamon Syakti (Politeknik Bisnis Indonesia, 2023)
The large number of requests from students applying for scholarships in the Achievement and Bidikmisi pathways means that the school's performance is still not optimal, because the process of collecting and filtering data on scholarship receipts is still manual. Decision support systems are useful in processing data or obtaining information and can help solve problems, especially in various very complex and unstructured issues. The SAW (Simple Additive Weighting) method is a decision support system method that can process scholarship selection results automatically through a system that has been created so that the results are fast and accurate. This research was carried out at Taman Siswa Middle School, Palembang. Researchers collected data through observation, interviews, and literature study. System analysis uses a cause-and-effect analysis method based on existing data, with the development of a waterfall system and HTML and PHP programming languages. The research results show that the highest final score close to score 1 processed by the support system is a student who is recommended to receive a scholarship, while students with the lowest final score are students who are not recommended or not worthy of receiving a scholarship. The Decision Support System in selecting PPA and Bidikmisi scholarship recipients using the SAW method succeeded in determining the order (priority) of students who were entitled and worthy of receiving the scholarship.